Faktor - Faktor Yang Berhubungan Dengan Pengetahuan Ibu Hamil Di Masa Pandemi Covid-19 Terhadap Pemberian Asi - Sumarti (Indonesian Journal of Midwifery Scientific, 2022)
Abstract Factors Related to Knowledge of Pregnant Women During the Covid-19 Pandemic on Breastfeeding. Breastfeeding during the Covid-19 pandemic must be maintained (UNICEF and WHO, 2020). The lowest breastfeeding was in Central Africa, North Africa, Asia, and Latin America (RI Ministry of Health, 2010). The small number of rates of exclusive breastfeeding globally and in Indonesia has gotten worse with the Covid-19 pandemic (Peng et al., 2020). This study aims to determine the knowledge of pregnant women during the Covid-19 pandemic regarding breastfeeding at PMB Anna Haifani Karang Tengah, Tangerang City in June 2021. Data collection based on primary data was taken by means of a questionnaire survey. The population is 30 pregnant women in June. Data analysis uses Chi Square with a significance of α (0.05). The results of 30 respondents showed mothers who had less knowledge 17 (56.7%), and pregnant women with healthy reproductive age 19 (63.3%), and mothers with higher education 17 (56.7%), and mothers with jobs not worked 20 (66.7%), and had never breastfed 16 (53.3%), and mothers received support 19 (63.3%). Bivariate analysis showed that there was a significant relationship between Age P = 0.000, Education P = 0.000, Family Support P = 0.007. To increase the knowledge of pregnant women during the Covid-19 pandemic regarding breastfeeding, counseling on breastfeeding should be carried out during the Covid-19 pandemic.